2015
DOI: 10.1111/hepr.12570
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the cost‐effectiveness of daclatasvir plus asunaprevir in difficult to treat Japanese patients chronically infected with hepatitis C genotype 1b

Abstract: Cost-effectiveness conclusions are similar for patients treated in the chronic hepatitis C and CC disease stages, with DCV + ASV expected to be cost-saving versus standard of care in Japan for patients with HCV genotype 1b patients who have failed prior therapy or are IFN-ineligible/intolerant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 28 publications
0
19
0
1
Order By: Relevance
“…Although DCV/ASV dual therapy has not been approved to treat HCV infection everywhere in the world, and ledipasvir/sofosbuvir is the first-line therapy, DCV/ASV dual therapy has clinical importance in Asian countries such as Japan, China, Korea, and Taiwan. In Japan, DCV/ASV dual therapy is expected to be cost-saving for patients with HCV genotype 1b who have failed prior therapy or are IFN-ineligible/intolerant [31]. In addition, DCV/ASV dual therapy for chronic hemodialysis patients with HCV infection is highly effective and well tolerated, even for elderly patients and patients with liver cirrhosis or the resistance-associated variant NS5A-Y93H at baseline [32].…”
Section: Discussionmentioning
confidence: 99%
“…Although DCV/ASV dual therapy has not been approved to treat HCV infection everywhere in the world, and ledipasvir/sofosbuvir is the first-line therapy, DCV/ASV dual therapy has clinical importance in Asian countries such as Japan, China, Korea, and Taiwan. In Japan, DCV/ASV dual therapy is expected to be cost-saving for patients with HCV genotype 1b who have failed prior therapy or are IFN-ineligible/intolerant [31]. In addition, DCV/ASV dual therapy for chronic hemodialysis patients with HCV infection is highly effective and well tolerated, even for elderly patients and patients with liver cirrhosis or the resistance-associated variant NS5A-Y93H at baseline [32].…”
Section: Discussionmentioning
confidence: 99%
“…Medical costs were estimated according to McEwan et al 12) Model and Parameters The simulation in this study used a Markov model. The model and parameters were based on the model described by McEwan et al, 12,13) "modeling the natural history and cost-effectiveness of hepatitis" (MONARCH), defined as the standard method in the review of HCV costeffectiveness studies (published in the period of 2000-2011). 14) In addition, Kamae et al 9) suggested several points to consider when using the MONARCH model in Japanese patients.…”
Section: )mentioning
confidence: 99%
“…SVR comp-LC (first year only) 122873 McEwan et al 13) 0.960 Ishida et al 20) CH monitoring 119576 McEwan et al 13) 0.920 Ishida et al 20) CH care 97610 McEwan et al 13) comp-LC monitoring 171090…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…There have been numerous cost‐effectiveness analyses suggesting that the use of DAAs is cost‐effective in treating CHC patients in western countries . However, only limited Asian reports are available . Moreover, owing to the high drug costs of DAAs and the lower affordability of people from less developed countries, whether one should use DAAs directly in naïve patients or only for retreatment remains unclear.…”
Section: Introductionmentioning
confidence: 99%